The French Revolution and the London stage, 1789-1805 - Taylor, George 1940- (Cambridge University Press, 2000)
During the French Revolution most performances on the London stage were strictly censored, but political attitudes found indirect expression. New and popular genres like pantomime, gothic drama, history plays, musical and spectacular entertainment, and, above all, melodrama provided metaphors for the hopes and fears inspired by the conflict in France and subsequent European wars. This 2001 book looks at how British drama and popular entertainment were affected by the ideas and events of the French Revolution and Napoleonic Wars. He argues that melodrama had its origins in this period, with certain gothic villains displaying qualities attributed to Robespierre and Napoleon, and that recurrent images of incarceration and dispossession reflected fears of arbitrary persecution, from the tyranny of the Bastille to the Jacobin's Reign of Terror. By a cultural analysis of the popular entertainment and theatre performances of the eighteenth and nineteenth centuries Taylor reveals issues of ideological conflict and psychological stress
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1700-1800; Geschichte 1800-1900; Geschichte 1789-1805; Geschichte; Theater / England / London / History / 18th century; Theater / England / London / History / 19th century; English drama / 18th century / History and criticism; English drama / 19th century / History and criticism; Englisch; Theater; Drama; Französische Revolution; Frankreich; France / History / Revolution, 1789-1799 / Influence; France / History / Revolution, 1789-1799 / Foreign public opinion, British; France / History / Revolution, 1789-1799 / Literature and the revolution; London